A 41-Year-Old Patient with a Rare Cause of Severe Abdominal Sepsis Misdiagnosed as PID - Anastasia Mikuscheva; David Becker; Mark Thompson-Fawcett (Case Reports in Surgery)
Infectious pelvic inflammatory disease is a common condition and a frequent cause of abdominal pain in a young female patient. In a patient who has not completed family planning, the diagnosis is often made with a low threshold and treatment started on a low suspicion of diagnosis to avoid a negative impact on fertility. Here, we present a case of a 41-year-old woman who was misdiagnosed with infectious pelvic inflammatory disease and treated ineffectively with antibiotics when the underlying condition of her persistent abdominal pain was a midgut neuroendocrine tumor that had caused bowel perforation and formation of an abscess in the pouch of Douglas.